2021
DOI: 10.1007/s40279-021-01604-9
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Squeeze on Compression Garments: Current Evidence and Recommendations for Future Research: A Systematic Scoping Review

Abstract: Background Compression garments are regularly worn during exercise to improve physical performance, mitigate fatigue responses, and enhance recovery. However, evidence for their efficacy is varied and the methodological approaches and outcome measures used within the scientific literature are diverse. Objectives The aim of this scoping review is to provide a comprehensive overview of the effects of compression garments on commonly assessed outcome measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 182 publications
(728 reference statements)
2
30
0
Order By: Relevance
“…Furthermore, the results of this study also suggest that a CG covering larger compared with smaller body areas appear to be more effective [19]. In sum, a recently published scoping review [20] concluded that while CGs are likely to improve muscle oscillatory properties, increase arterial blood flow and local skin temperature, facilitate signal transmission in the sensorimotor system, and may reduce perception of exercise-induced muscle soreness and pain, it is unlikely that CGs can meaningfully alter tissue metabolism, blood pressure, heart rate, and cardiorespiratory function.…”
Section: Introductionsupporting
confidence: 57%
“…Furthermore, the results of this study also suggest that a CG covering larger compared with smaller body areas appear to be more effective [19]. In sum, a recently published scoping review [20] concluded that while CGs are likely to improve muscle oscillatory properties, increase arterial blood flow and local skin temperature, facilitate signal transmission in the sensorimotor system, and may reduce perception of exercise-induced muscle soreness and pain, it is unlikely that CGs can meaningfully alter tissue metabolism, blood pressure, heart rate, and cardiorespiratory function.…”
Section: Introductionsupporting
confidence: 57%
“…Considering the importance of testing for coaches and athletes, it is essential to consider why and how the testing is being implemented. While the growing acceptance of sports science and technology has helped to continue the development and innovation within strength and conditioning (85,99), it has also led to extremely large amounts of data often being available (56). This can cause practitioners to be overwhelmed with information (i.e., “paralysis through analysis”), select inappropriate testing methods or outcomes (i.e., the lack of understanding of the test and its underpinning physiological/biomechanical constructs), or cause “testing for testing's sake.” Thus, understanding the “why” can support decisions around what information is retained and help determine the purpose, which in turn can help guide the tests that are selected.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, further studies additionally reported the potential benefits of compression garments in improving blood circulation, muscle fatigue, and recovery in post-exercise [3]. Common types of compression sportswear include shirts, shorts, sleeves, socks, and underwear, typically made of an elastic material so that the compression sportswear may be beneficial for improving physiological, biomechanical, and subjective components during and after exercises [4,5]. For example, the use of lowercompression sportswear reduced blood lactate, blood flow, and heart rate during endurance exercises [6][7][8].…”
Section: Introductionmentioning
confidence: 99%